2015
DOI: 10.5897/ajmr2015.7662
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance pattern of Salmonella and Shigella species isolated from selected hospitals in Anyigba, Kogi State, Nigeria

Abstract: This work was designed to assess the status of Salmonella and Shigella infections in Anyigba, Kogi State, Nigeria with a view to making informed statements that may guide policy makers and public health experts in the containment efforts against these infections. Salmonella and Shigella species isolated from human faecal samples were examined for resistance to some antibiotic agents using disc diffusion methods. Drug resistant isolates were analyzed for presence of plasmids by basic curing and transferability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Antimicrobial resistance genes that pose the most significant threat to human medicine are typically found in Gram-negative bacteria (Michelle et al 2018). Previous reports have shown that drug resistance of Salmonella is an emerging global challenge, especially in low-and middle-income countries where misuse and abuse of antimicrobial agents are on the increase (Ocean et al 2015). Furthermore, the emergence and spread of plasmidborne resistance genes that undergo horizontal gene transfer are threatening many last-line antibiotic therapies (Crofts et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance genes that pose the most significant threat to human medicine are typically found in Gram-negative bacteria (Michelle et al 2018). Previous reports have shown that drug resistance of Salmonella is an emerging global challenge, especially in low-and middle-income countries where misuse and abuse of antimicrobial agents are on the increase (Ocean et al 2015). Furthermore, the emergence and spread of plasmidborne resistance genes that undergo horizontal gene transfer are threatening many last-line antibiotic therapies (Crofts et al 2017).…”
Section: Discussionmentioning
confidence: 99%